ANALISIS KESULITAN GURU DALAM MENGEMBANGKAN INDIKATOR PEMBELAJARAN KURIUKULM 2013 SDN 210 BOTTOPENNO - Ryaas Rasyd; Muhammad Amran; Satriani Satriani; Rosdiah Rosdiah (Autentik : Jurnal Pengembangan Pendidikan Dasar, 2021)
The research question in this study is how difficult the teacher is in developing the 2013 Curriculum Learning Indicators at SDN 210 Bottopenno. This research is a qualitative research with research subjects namely teachers of grades I, II, III, IV, V, and VI. Data collection using interview guidelines and documentation. Data analysis techniques are data reduction, data presentation stage, and drawing conclusions. The results obtained are that the teacher has difficulty in translating KD into indicators, determining the appropriate Operational Verbs (KKO), determining and adjusting competencies according to the characteristics of students, identifying the abilities of students, determining learning activities according to the indicators made, determining the type of assessment that is in accordance with the indicators applied, and the lack of training regarding the preparation of the 2013 Curriculum RPP that is in accordance with the conditions and characteristics of each region. The conclusion in this study is that the teacher of SDN 210 Bottopenno class in developing teacher learning indicators has difficulty in 1) describing basic basic competencies, 2) determining KKO, 3) determining competence, 4) identifying student characteristics, 5) determining learning activities, 6) determining the type of learning activity. assessment and 7) lack of 2013 Curriculum training in accordance with the conditions and characteristics.